Cardiac assessment of limb–girdle muscular dystrophy 2I patients: An echography, Holter ECG and magnetic resonance imaging study - Wahbi, Karim; Meune, Christophe; Hamouda, El Hadi; Stojkovic, Tania; Laforêt, Pascal; Bécane, Henri Marc; Eymard, Bruno; Duboc, Denis (Neuromuscular disorders : NMD, 2008)
Mutations in the FKRP gene may be associated with cardiac involvement. The aim of our study was to assess myocardial involvement in patients with LGMD2I, using physical examination, echocardiography, resting and 24-h ambulatory electrocardiogram and cardiac magnetic resonance imaging, with particular attention to the detection of myocardial morphologic abnormalities. Patients were compared to matched controls. Twenty-three patients were enrolled (men 10 – women 13; 32.3 ± 9.5 years). Twenty-two had the C826A gene mutation (homozygous 12, heterozygous 10). Nine patients had severe muscle alterations, 10 had milder muscle involvement and 4 had isolated exertional myoglobinuria. When compared to controls, LGMD2I patients had reduced left ventricular ejection fraction (50.8 ± 13.9 versus 66.6 ± 3.8%, p < 0.0001). Sixty percent of patients had reduced left ventricular ejection fraction, including 8% with severe reduced left ventricular ejection fraction <30%. None had significant arrhythmia. Gene mutation and the severity of the muscle disease were not predictive of cardiac involvement. Cardiac magnetic resonance imaging displayed a high prevalence of myocardial functional abnormalities, fatty replacement and fibrosis, among the 13 patients investigated. Reduced contractility and cardiac magnetic resonance imaging morphological abnormalities are highly prevalent in LGMD2I patients suggesting that all patients should be referred for cardiac evaluation.